Association between melanin and vitamin D: A systematic review - Andre Colin Hartono; Veronika Maria Sidharta; Yunisa Astiarani; Regina Regina (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Globally, there is an increasing prevalence of vitamin D deficiency, including in Southeast Asia, which ranges from 6% to 70%. Vitamin D plays an important role in calcium metabolism and bone health. Melanin is one factor that contributes to vitamin D deficiency. It has photoprotective properties that inhibit vitamin D synthesis, but the mechanism has not been fully understood. To determine the mechanism of the association between melanin and vitamin D, this systematic review was conducted on 11 articles, including cross-sectional studies, cohort studies, and randomised controlled trials published from 2010 to 2020. The search included Pubmed, EBSCO, and Proquest databases, and data were synthesised from 11 studies. This critical review found nine of the 11 studies reported a significant association between melanin and vitamin D, while two reported non-significant results. Of the nine significant studies, eight reported that people with higher melanin have lower vitamin D levels, while one study suggested that melanin levels do not necessarily associate with lower vitamin D levels. In conclusion, the review establishes a significant association between melanin and vitamin D.